The Effectiveness of the Role of Parenting on the Decision to Determine the Further Education of Students - Pelita, Della; Lubis, Saiful Akhyar; Darmayanti, Nefi (Ilomata International Journal of Social Science, 2024)
This research investigates the effectiveness of the parenting role in the context of decision making regarding further education for students in Islamic boarding schools. This research was conducted to understand how the care provided by Islamic boarding school caregivers influences students' decisions in choosing further education. A qualitative approach was used with in-depth interview techniques with caregivers and students to collect data. Data analysis was carried out using the content analysis method to identify the main themes in parenting that have an impact on students' further education decisions. The findings of this study provide insight into the parenting factors that are significant in the decision-making process of students regarding their further education. The implications of the results of this research can be used to improve understanding and approaches to care in Islamic boarding schools to support better further education decision making for students.